PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. CIMB NIAGA JAKARTA PUSAT - Bagus Saputra; Pancagaluh Ratnasih (Journal of Research and Publication Innovation, 2025)
This research aims to analyze the influence of work motivation and work discipline on employee performance at PT. CIMB Niaga Central Jakarta. According to Andika (2019:190)